2014
DOI: 10.1128/jvi.02428-14
|View full text |Cite
|
Sign up to set email alerts
|

Linking Pig-Tailed Macaque Major Histocompatibility Complex Class I Haplotypes and Cytotoxic T Lymphocyte Escape Mutations in Simian Immunodeficiency Virus Infection

Abstract: The influence of major histocompatibility complex class I (MHC-I) alleles on human immunodeficiency virus (HIV) diversity in humans has been well characterized at the population level. MHC-I alleles likely affect viral diversity in the simian immunodeficiency virus (SIV)-infected pig-tailed macaque (Macaca nemestrina) model, but this is poorly characterized. We studied the evolution of SIV in pig-tailed macaques with a range of MHC-I haplotypes. SIV mac251 genomes were amplified from the plasma of 44 pig-taile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Ancestral‐like MHC haplotypes also appear to exist in mice and macaques . The macaque MHC class I, class II and/or entire MHC haplotypes were estimated using the MHC allele and/or pedigree information in each species such as Mafa , Mamu and Mane . Copy number variations of the MHC‐A , MHC‐E , MHC‐B , MHC‐I and MHC‐DRB loci were observed in the different macaque species, similar to the HLA‐DR haplotype .…”
Section: Mhc Polymorphism and Haplotype Structurementioning
confidence: 98%
“…Ancestral‐like MHC haplotypes also appear to exist in mice and macaques . The macaque MHC class I, class II and/or entire MHC haplotypes were estimated using the MHC allele and/or pedigree information in each species such as Mafa , Mamu and Mane . Copy number variations of the MHC‐A , MHC‐E , MHC‐B , MHC‐I and MHC‐DRB loci were observed in the different macaque species, similar to the HLA‐DR haplotype .…”
Section: Mhc Polymorphism and Haplotype Structurementioning
confidence: 98%
“…Another advantage of defining full-length ORF sequences is in regards to restriction of infectious diseases. Previous studies have identified multiple MHC-I variants that bind to specific epitopes of SIV (Gooneratne et al 2014). In this study, we identified multiple closely related allelic variants of these MHC-I gene products that have been documented to restrict SIV epitopes.…”
Section: Advantages Of Using Full-length Cdna Sequencing Over Short Gmentioning
confidence: 92%
“…MHC class I genotyping was carried out as described previously (41)(42)(43). Total cellular RNA was isolated from whole blood or PBMCs, and first-strand cDNA was synthesized by reverse transcription with SuperScript III (Life Technologies, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Of these 19 controlling animals, 15 exhibited levels below detection (Յ15 or 50 copies/ml using a standard assay or a more sensitive assay), with the other 4 animals showing persisting but low level viremia with intermittent RNA increases of 10 2 to 10 3 copies/ml. Deep-sequencing analysis showed that animals in both the ⌬GY and SIVmac239 challenge groups carried a diverse array of MHC haplotypes ( Table 1), indicating that differences in control of chronic-phase viral replication were unlikely to be associated with MHC class I genetics, including the Mane-A084 allele (formerly Mane-A*10), which has been implicated as an SIVmaccontrolling allele in pig-tailed macaques in early (54) although not more recent (41,55) studies. Viral set points for ⌬GY-controlling pig-tailed macaques were also reduced compared to those in 4 previously described ⌬GY-infected rhesus macaques (P Ͻ 0.01), which had RNA levels of 3.8 ϫ 10 4 Ϯ 1.4 ϫ 10 4 copies/ml and progressed to disease (Fig.…”
Section: Viral Dynamics Of ⌬Gy Infection In Pig-tailed Macaquesmentioning
confidence: 99%